CURSOS SUPERIORES DE TECNOLOGIA NO GRANDE ABC PAULISTA: PERCEPÇÃO DOS ALUNOS E PROFESSORES - Guets, Moacir (2008)
The aim of this paper is to analyse the perception of the students, professors and job market about the technological courses offered by colleges and universities from ABC paulista and the historical research about this profession. Through this analysis we could have the conception of this course and it was integrated by the current brazilian society. It is represented by the region of ABC paulista and questions about social, economic and cultural conditions of these students besides the analysis of the accomplished interview with students, professors and current works. Summing up it was possible to identify the ingress and egress profile of the students since all the possible mechanisms are indicated for this formation.(AU)